Frequency of Prenatal Care Uptake and the Factors Affecting it in the 15-49 Age Group, and to Evaluate the Suitability of the Service Provided. - Ozlem KARABULUTLU; Gulhan AKDEMIR (Atatürk University, 2021)
Aim: The aim of this study was to evaluate the factors affecting and the frequency of uptake of prenatal care by pregnant women aged 15-49, and to evaluate the suitability of the service provided. Method: The sample of the cross-sectional study consisted of 200 pregnant women who attended the Gynecology and Obstetrics Clinic of Iğdır State Hospital between February and July 2018 and agreed to participate in the study. A "Personal Information Form", an "Evaluation Form for Examination and Tests to be Performed in Prenatal Care" and an "Evaluation Form for Training and Counseling Services in Prenatal Care" were used for data collection. In the analysis of the data, frequency, percentage, mean and standard deviation were calculated and Pearson's Chi-squared Test and Fisher's Exact Test were used. Results: While the rate of receiving adequate prenatal care is 83%, the rate of pregnant women who find the prenatal care they receive qualified is 40.5%. In the study, statistically significant relationships were found between the frequency of uptake of prenatal care and the number of pregnancies, the type of family, the number of children living, consanguineous marriage and the number of spontaneous or induced abortions (p<0.05). No statistically significant relationships were found between the frequency of uptake of prenatal care with the age, the age at first marriage or the age at first gestation of the pregnant woman, with having had an arranged marriage, a planned pregnancy, or a stillbirth, with the death before age 5 of a child born alive, with place of residence, with being in receipt of social security benefit, with the level of education of the pregnant woman and her spouse, with the pregnant woman and her spouse having a regular income from employment or with the family's economic status (p˃0.05). Conclusion: In the study group, the proportion of pregnant women who evaluated the care they received as being of sufficient quality was lower than the proportion of pregnant women who received an adequate amount of prenatal care. In order to provide a service that is of sufficient quantity and quality, in the guide for prenatal care, due importance should be given to the examination, treatment and trainings of pregnant women.